A Self‐Assembled Nanohybrid Composed of Fluorophore–Phenylamine Nanorods and Ag Nanocrystals: Energy Transfer, Wavelength Shift of Fluorescence and TPEF Applications for Live‐Cell Imaging1. Issue 49 (6th November 2013) - Kong, Lin; Yang, Jia‐xiang; Li, Sheng‐li; Zhang, Qiong; Xue, Zhao‐ming; Zhou, Hong‐ping; Wu, Jie‐ying; Jin, Bao‐kang; Tian , Yu‐peng
Abstract A fluorophore–phenylamine derivative (L) has been coupled with silver nanocrystals (NCs) to construct an L–Ag nanohybrid. Owing to synergic effects of the L and Ag components, the exciton–plasmon interactions between L and Ag increase the strength of the donor–acceptor interaction within the nanohybrid, a fact that results in an energy‐transfer process and further brings about a dramatic redshift of single‐photon absorption and fluorescence, and a decreased fluorescence FL lifetime. The coupling effect also leads to enhancement of a series of nonlinear optical properties, including two‐photon‐excited fluorescence (TPEF), two‐photon‐absorption (TPA) cross section (δ), two‐photon‐absorption coefficient (β), nonlinear refractive index (γ), and third order nonlinear optical susceptibility (χ(3)). The enhanced two‐photon fluorescence of the nanohybrid is proven to be potentially useful for two‐photon microscopy of live cells, such as HepG2. Moreover, cytotoxicity tests show that the low‐micromolar concentrations of the nanohybrid do not cause significant reduction in cell viability over a period of at least 24 h and should be safe for further biological studies.